Territorialidades audiovisuais e deslocamentos: os protagonistas negros no cinema de Quentin Tarantino - Rocha, Delio Freire (2019)
The racial question is present in the origin of the cinema with the film The Birth of a Nation (1915), by D.W. Griffith, characterizing the cinematographic field as a scenario of dispute of the representation of blackness from its beginning to the present day. In the mid-1940s, during the postwar period, popular film genres such as Western and Noir began to become popular and to become more complex, bringing a dialogue with contemporary issues. In the following decades, variations of this genre were presented by artists and researchers such as Metawestern, Western Spaguetti, Blaxploitation, and Neo-noir. In this work, a survey of theoretical texts demonstrating and interpreting the processes of discourse and centrality of black characters in the works of Quentin Tarantino is done, as well as the director dialogues, appropriates and reinvents the Western and Noir genres and their variations, obtaining with this a prominent position in the North American film field. From the observation and interpretation made around a bibliography on the representation of the Negro in American cinema, from the categories of racism and black protagonism (Achille Mbembe) and the Eurocentric image (Robert Stam, Ella Shohat), and from the field theory (Pierre Bourdieu), and the analysis of the films Jackie Brown (1997) and Django Livre (2012), conducted in the United States from 1997 to 2012, we present the hypothesis that Quentin Tarantino's filmography seeks to bring to the center of the film discussion racial issues and representation. Quentin Tarantino incorporates in his cinematic realization the black culture, the racial formation in the United States and the institutionalized racism. The objective of the filmmaker, as the present research wants to demonstrate, is the development of a symbolic territoriality where the black personage obtains protagonism in his narratives